A Comparative Study on the Role of Stochastic Trends in U.S. Macroeconomic Fluctuations, 1954-1988 - Atilim Seymen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
The paper attempts to provide an appropriate model specification for identifying technology and other macroeconomic shocks in a structural VAR framework. The investigation is conducted based on two seminal structural VAR studies by Gali (1999) and King et al. (1991). The models of these studies are compared and contrasted, and then modified based on the findings. The analysis builds on two studies of Alexius and Carlsson (2001, 2005) that examine the ability of structural VAR models to identify technology shocks. The original and augmented models are used for investigating the driving forces behind business cycle fluctuations.
Keywords: C32; C51; C52; 330; Structural Vector Autoregression; Long-Run Restrictions; Error Variance Decomposition; Konjunktur; Schock; VAR-Modell; USA